2019
DOI: 10.1007/s40519-019-00667-y
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based emotional eating awareness training: taking the emotional out of eating

Abstract: Purpose Emotional eating is important to study and address because it predicts poor outcome in weight loss interventions. Interventions have only touched the surface in terms of addressing emotional eating. Mindfulness approaches can address emotional eating by modification of emotion regulation and appetitive traits. The current study involved development of an emotional eating-specific mindfulness intervention and assessment of its effect on appetitive traits associated with emotional eating. Methods Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 69 publications
(127 reference statements)
3
31
0
8
Order By: Relevance
“…Whilst other research designs are suited to mixed assessments of alexithymia via observer-reported alongside self-reported measures, online questionnaires can only make use of self-report measures. Furthermore, the emotional eating construct is multifaceted and influenced by context meaning it is not fully captured by questionnaire measures ( Lattimore, 2020 ). The present study utilised the EES and SEES which measure self-reported emotional eating urges and behaviours respectively, to garner a wider measurement of the emotional eating construct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst other research designs are suited to mixed assessments of alexithymia via observer-reported alongside self-reported measures, online questionnaires can only make use of self-report measures. Furthermore, the emotional eating construct is multifaceted and influenced by context meaning it is not fully captured by questionnaire measures ( Lattimore, 2020 ). The present study utilised the EES and SEES which measure self-reported emotional eating urges and behaviours respectively, to garner a wider measurement of the emotional eating construct.…”
Section: Discussionmentioning
confidence: 99%
“…Eating in response to emotions can be positive for some individuals, as it is context-dependent ( Lattimore, 2020 ). It has been found to buffer the association between adverse life events and perceived stress, but only in individuals without elevated levels of depressive symptoms ( Finch & Tomiyama, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, during the COVID-19 pandemic, eating can, on the one hand, help to cope with the current difficult situation and the negative emotions associated with it; on the other hand, frequent use of this tendency can lead to rigid regulation of affect and use of this mechanism as the dominant mechanism [ 11 , 12 , 13 , 37 , 56 ]. Therefore, limited social contact, related disruptions in daily activities and stress resulting from COVID-19 should generate appropriate interventions, not necessarily focusing only on emotional eating, but also on the resources of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…The index known as SSRT has been used to indicate impulsivity (a lack of cognitive control) in prisoners (Bell & Polaschek, 2017). This index has also been used when assessing the impact of mindfulness in general population cohorts (Lattimore, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that within general population samples, engaging in “mindful breathing” can increase HRV (Burg et al, 2012), as can a 4-week mindfulness intervention (Shearer et al, 2016). In relation to cognitive control, behavioral measures gathered via computer based tasks have also been shown to be sensitive to change following mindfulness interventions in research examining “emotional eating” (Lattimore, 2020). Thus supplementing self-report with physiological (HRV) and computer based reaction time/accuracy assessment would enhance the robustness of the measurement available.…”
Section: Limitations With the Existing Criminal Justice Based Evidencementioning
confidence: 99%